The rider - Zhao, Chloé; Jandreau, Brady; Jandreau, Tim; Jandreau, Lilly (Culver City, California : Sony Pictures Home Entertainment, 2018)
After suffering a near fatal head injury, a young cowboy undertakes a search for new identity and what it means to be a man in the heartland of America.
Title from web page.
Originally released as a motion picture in 2017.
Special features: Q&A featuring Chloe Zhao, Brady Jandreau, Joshua James Richard & Alex O'Flinn ; deleted scenes ; Q&A with Brady Jandreau.
Brady Jandreau, Tim Jandreau, Lilly Jandreau.
Rating: R; for language and drug use : CHV rating: 14A.
DVD, region 1, wide screen (2.39:1); Dolby digital 5.1; described video.
Keywords: Western films